Eastern Europe as the source of horror and humor: Examples films, "Hostel" and "Euro Trip" - Vesna Trifunović (University of Belgrade, 2016)
In the period from 2004. to 2007. three films belonging to two different genres were complete in the American production-a horror and a comedy. These being, Hostel (I and II) and Euro Trip. The only similarity found in these films is the same stimulus that motivates the horror and the humor segment in them. That stimulus was identifies where all three films are placed, and that is Eastern Europe, more precisely Slovakia. This phenomenon was considered in Noel Carroll’s theory concerning the relationship of horror and humor in order to explain and understand their existence.